ABOUT NEW APPROACHES IN ASSESSING THE QUALIFICATIONS OF IT-SPECIALISTS - Abdiyev, К.С.; Yeskendirova, Д.М.; Zhassandykyzy, М.; Primbetova, Г.С. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2023)
The main goal of the study conducted by the authors of the article is to develop a model for internal assessment of the level of professional competence of undergraduate graduates. Assessment of the level of competencies at the stage of formation at the university can become part of the system for preparing graduates for qualification exams. According to the draft Law of the Republic of Kazakhstan “On professional qualifications”, confirmation of qualifications should be carried out by employers. To determine the form and content of the developed internal assessment system, a content analysis of articles and documents describing the existing qualification exams in the field of medicine and health care in the Russian Federation and Kazakhstan, an independent assessment of the qualifications of IT specialists in the Russian Federation, and Assessment of the knowledge of teachers in Kazakhstan was carried out. The analysis of the content of the professional standards of the IT industry of Kazakhstan, international documents describing the qualification requirements for IT specialists was also carried out. The universities of Kazakhstan have not yet gained experience in using the professional standards of the IT industry in the development of educational programs. Matching the content of educational programs of universities with the requirements for professional skills, reflected in industry standards, should become the basis for preparing graduates for confirmation of qualifications in independent centers.